Global Entrepreneurship Monitor Caribbean 2011 : Colombian national report (2012)
A broad agreement exists today among the academia and public policy makers about the importance of entrepreneurial activity and entrepreneurs in the dynamics of economic development. New businesses drive innovation, generate jobs and, stimulate productivity and competition thereby developing the economy and welfare of a society. The Global Entrepreneurship Monitor (GEM) is conducting the biggest on-going research worldwide in order to study and analyze the relationship that exists between entrepreneurship and the national economic development. This project started in 1999 as an initiative of Babson College and the London School of Economics. At the present time, it is the only comparable data source that exists globally about a wide range of variables associated with the general entrepreneurial activity and specific elements in the different stages that compose the entrepreneurial process.